2011
DOI: 10.1016/j.maturitas.2011.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Sexual satisfaction in the elderly female population: A special focus on women with gynecologic pathology

Abstract: Sexual function in aging women Sexuality is an integral part of human expressions. Mental health plays a major role in sexuality. Several psychological interventions are proposed to increase the sexual quality of life in older women with diverse gynecologic pathology. A biopsychosocial approach utilizing brief strategies can be easily implemented in clinics to help women of all ages increase their sexual quality of life. The impact of female pelvic floor disorders on sexual function in older women Female pel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 63 publications
4
45
0
1
Order By: Relevance
“…Similar empirical support has been obtained for the importance of mental health problems, particularly those related to depression and anti-depressant medication use (Dundon & Rellini, 2010;Kim & Jeon, 2013;McCall-Hosenfeld et al, 2008;Scott et al, 2012;Thompson et al, 2011;Wang et al, 2014). Finally, moderate to strong associations between sexual satisfaction and well-being, and sexual health disorders or impaired sexual function (Ratner, Erekson, Minkin, & Foran-Tuller, 2011) have been consistently observed (Heiman et al, 2011;Laumann et al, 2006;Traeen & Schaller, 2010). In addition to relatively frequent agerelated loss of sexual interest in both men and women (DeLamater et al, 2008), erectile problems among men and problems with lubrication, genital pain, and diminished orgasmic function were frequently found to negatively affect sexual satisfaction in older age (Field et al, 2013;Heiman et al, 2011;Laumann et al, 2006).…”
Section: Predictors and Correlates Of Sexual Satisfaction In Older Agesupporting
confidence: 59%
“…Similar empirical support has been obtained for the importance of mental health problems, particularly those related to depression and anti-depressant medication use (Dundon & Rellini, 2010;Kim & Jeon, 2013;McCall-Hosenfeld et al, 2008;Scott et al, 2012;Thompson et al, 2011;Wang et al, 2014). Finally, moderate to strong associations between sexual satisfaction and well-being, and sexual health disorders or impaired sexual function (Ratner, Erekson, Minkin, & Foran-Tuller, 2011) have been consistently observed (Heiman et al, 2011;Laumann et al, 2006;Traeen & Schaller, 2010). In addition to relatively frequent agerelated loss of sexual interest in both men and women (DeLamater et al, 2008), erectile problems among men and problems with lubrication, genital pain, and diminished orgasmic function were frequently found to negatively affect sexual satisfaction in older age (Field et al, 2013;Heiman et al, 2011;Laumann et al, 2006).…”
Section: Predictors and Correlates Of Sexual Satisfaction In Older Agesupporting
confidence: 59%
“…From previous studies, it is known that improvement or deterioration of sexual function after surgery seems to depend on the surgical technique used. 27 However, there is no information available about the surgical procedure that was used in women who underwent pelvic floor surgery and therefore it is hard to explain the association between pelvic floor surgery and sexual functioning. Although the current evidence on the influence of pelvic floor surgery on sexual function is still inconclusive, [28][29][30][31] pelvic floor surgery results in anatomic and functional changes in the pelvic floor area that potentially influence sexuality.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…However, health care providers often lack education concerning sexological issues, and their attitudes towards working to promote sexual health can be challenged by their own believed non-importance of sexual health for persons with disease or disability (Esmail, Darry, Walter, & Knupp, 2010;Low & Zubir, 2000). Sexual health is strongly related to feelings of well-being and general health (Field et al, 2013;Lindau & Gavrilova, 2010;Ratner, Erekson, Minkin, & Foran-Tuller, 2011), and previous research has shown that rehabilitation can promote sexual health (Kristina Areskoug- Josefsson & Gard, 2015;K. Areskoug-Josefsson & Oberg, 2009;Egan et al, 2013;Josefsson & Gard, 2012;Rosenbaum, 2006).…”
mentioning
confidence: 99%